Analysis of the Effect of Sound Dampening on Ship Engines Based on Tofu Dregs Composite Material (Glycine Max (L) Merill) - Wijaya, Belqis Risky; Ilmah, Aurista Miftahatul; Risdianto, Anauta Lungiding Angga; Prasetyo, Taufan; Iswidodo, Windra; Sahari, Sahari (Jurnal Fisika Papua, 2024)
Noise in the engine room of a ship is a significant problem that can affect the health and comfort of crew members. This study aimed to evaluate the potential of tofu dregs as a sound insulation material in the form of a composite of carbon black and talak duco. The research method included making composite specimens with variations in composition, followed by testing the sound absorption coefficient using the impedance tube method. The results showed that the specimen with 30% tofu dregs, 45% carbon black, and 25% talak duco produced the highest sound absorption coefficient of 0.24. These findings show that tofu dregs have potential as an environmentally friendly and economical sound insulation material and can be used to reduce noise in ship engine rooms. This study contributes to the development of natural fiber-based insulation materials in the maritime industry.